Raven's revenge - Masters, Anthony, 1940-2003 (Graphic quest, 2007)
When Andy goes kayaking at Greystone Grange, he hopes to forget about the nightmares he's been having, but on the wild river he discovers that real life can be a lot scarier than bad dreams.